Third Swiss Annual Meeting on HER2-Positive Breast Cancer: Recent Advances and New Challenges - Marcus Vetter; Christian Kurzeder (healthbook TIMES. Oncology Hematology)
The development of antibody-based therapies has transformed the treatment of human epidermal growth factor receptor 2 (HER2)-positive breast cancer. More recently, HER2-directed antibody-drug conjugates (ADCs) have demonstrated efficacy in HER2-negative breast cancer patients who had a certain level of HER2 expression (HER2 low). The Third Swiss Annual Meeting on HER2-positive breast cancer held in Basel, Switzerland, on April 11, 2024, has brought together leading experts in the field of oncology to discuss the latest advancements and challenges in this clinical setting. This paper summarizes the key messages from the meeting.